Changes in ARB Sputum Positivity, BMI and TNF-? Levels of Pulmonary TB Patients with ARB Positive During One-month Intensive Treatment - Samsuri1, Helmia Hasan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Backgoround: TNF-? plays a role in the occurrence of anorexia and weight loss in pulmonary tubercolusis (TB) patients. Evaluation of treatment response can be done with clinical, microbiological and radiological evaluation. In patients without cough, Body Mass Index (BMI) and TNF-? levels can be used to evaluate clinical treatment response. Objectives: The aim of the study is to measure the Acid Resistant Bacteria (ARB) sputum positivity decrease, TNF-? levels and increased BMI after 2 weeks and 4 weeks intensive treatment of pulmonary TB patients with new case of ARB positive. Methods: The sample size was 14 people with ARB positive pulmonary TB cases, consisting of 9 men and 5 women. It was done sputup smear, BMI and TNF-? examination before treatment, at week 2 and week 4 of intensive phase treatment Result: At the end of the second week, TNF-? levels decreased significantly compared to baseline TNF-? levels with p = 0.015. There was a non significant increase of BMI at the end of the second and fourth week with p = 0.309 and p = 0.270 respectively. The decrease in ARB sputum smear positivity at the end of the second week compared to the fourth week was not statistically significant with p = 0.157. There was a strong correlation between TNF-? and IMT levels before treatment with negative correlation, r = -0.702 and p = 0.005. Conclusion: Levels of TNF-? at the end of the second week decreased significantly compared to baseline TNF-? levels. There was a strong correlation between TNF-? levels and BMI prior to treatment.